TSHR in thyroid cancer: bridging biological insights to targeted strategies - Shaojie Xu; Youyun Peng; Xingyin Li; Hanning Li; Ting Liu; Xingrui Li; Yaying Du (European Thyroid Journal, 2025)
Traditionally, thyroid-stimulating hormone receptor (TSHR) has been utilized primarily to increase the efficacy of radioactive iodine therapy by promoting iodine uptake. However, the rise of personalized medicine has prompted reassessment of the potential of TSHR as a therapeutic target. Recent studies have indicated that TSHR plays a critical role in the progression of thyroid cancer and may serve as a key target for the treatment of residual or metastatic thyroid cancers, particularly radioiodine-refractory differentiated thyroid cancer (RAIR-DTC). This review focuses on the biological characteristics of TSHR and its potential as a therapeutic target, emphasizing that optimizing TSHR-targeted drugs and integrating them with existing treatment strategies could offer new therapeutic avenues for patients with RAIR-DTC.